Clinical and laboratory features of COVID-19 in children - Madjidova Yo.N; Temirova M.K; Azimova N.M; Nurmatov A.Kh; Khusanov A.M (Genius Journals, 2023)
The new coronavirus infection has revealed the shortcomings of the global medicine system. To date, Covid-19 and its complications remain the most relevant for all medical specialties. The article reveals the relevance of the problem of coronavirus infection in children, investigated the risks of the disease, symptoms according to age ranges, considered options for the severe course of the disease and their prevention
Keywords: Covid -19; children Covid; post-covid syndrome